Russia Leaves the War. Vol. 1 of Soviet-American Relations - GEORGE FROST KENNAN (Princeton University Press, 2014)
WHEN this study was first contemplated, the intention was not to reconstruct in detail the happenings of the initial months of the Soviet- American relationship, but rather to attempt a critical appraisal of the actions and policies of the two governments in their relations with each other over a much longer span of time. It soon became apparent, however, that despite the existence of several valuable secondary works on individual phases of Soviet-American relations in the early period, there was no general treatment of this subject, tapping all the sources available today, that could serve as adequate foundation for critical judgment. In these circumstances there was no alternative but to delve into the original source materials and to attempt to unravel, if only for one's own instruction, the tangled web of what actually occurred. The present volume brings the first fruits of these researches, relating to the period between the November Revolution of 1917 and Russia's final departure, in March 1918, from the ranks of the warring powers. It is, admittedly, a heavily detailed account; some may think too much so. In attempting to bring together the available evidence on events at once so complex and so controversial, I have preferred to err on the side of explicitness rather than to run the risk, or invite the suspicion, of partiality in the selection of material. But beyond that: the more I saw of these records of the doings of an official generation slightly older than my own, the more it was borne in upon me that the genuine image of the diplomatic process is hardly to be recaptured in historical narrative unless the lens through which it is viewed is a sharp one and the human texture of which it consists becomes visible in considerable detail. The acts and decisions of statesmanship will seldom be found entirely intelligible if viewed apart from the immediate context of time and circumstance —information, associates, pressures, prejudices, impulses, and momentary necessities—in which they occur.